Exploring language bias in the NEO-PI-R - Franklin, Dee Ross (My University, 2010)
The study explores language bias in the NEO-PI-R both quantitatively and qualitatively. A sample of 28 postgraduate psychology student volunteers completed a questionnaire containing the NEO-PI-R and two open-ended questions about the instrument. These responses were then analysed across English first language and second language speakers to explore issues of bias. Reliability of the NEO-PI-R appeared to be robust at a domain level. The reliability of the facets, while appropriate for the most part, still yielded low alpha coefficients for the Excitement-seeking, Actions, Values and Straightforwardness facets. ANOVA’s at the domain and facet scale levels indicated no significant differences across home language. However ANOVA’s at the item level yielded 33 in total that were problematic, comprising of 12 items that were significant at the 5% level of significance and 21 items at the 10% level of significance. These items were primarily from the N and E domains. Thematic analysis of the open-ended questions of the questionnaire indicated 26 items were difficult to understand and/or inappropriate for the South African context. These items were primarily from the E and A domains. From the original sample of 28 volunteers, two focus groups were formed, comprising of volunteers from the initial sample. The focus groups explored several qualitative issues, including concepts of personality, language and culture and the applicability of the NEO-PI-R for South African user groups. It was perceived that there is a presence of American socio-cultural references within the use of language, grammar and socio-cultural context in the instrument. Thus the results show evidence of language bias in the NEO-PI-R, and subsequently identify particular aspects and items of the instrument that are especially problematic for a South African user group. The present study suggests that the NEO-PI-R would need to be revised to suit the South African context by changing the problematic items.
Keywords: Bias; Culture; Five-Factor Model; Language; NEO-PI-R; Personality